TANGGUNG JAWAB DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENERBITKAN AKTA KELAHIRAN MENGGUNAKAN SATU KATA DI KABUPATEN SEKADAU - NIM. A1011191039, NURUL AGUSTINE (Jurnal Fatwa Hukum, 2025)
Abstract This study analyzes the issuance of birth certificates bearing single-word names in Sekadau Regency, notwithstanding Article 5 Paragraph (3) of Minister of Home Affairs Regulation No. 73 of 2022, which stipulates that a name must consist of at least two words. The persistence of this practice is rooted in local traditions and beliefs that long names may become a burden for children or even cause illness, prompting parents to adopt single-word names instead. The research employs an empirical descriptive approach, with data obtained through interviews and questionnaires involving the Civil Registry Office (Disdukcapil) and parents during the period 2022"“2025. The data were analyzed qualitatively by correlating field practices with the prevailing legal framework. The findings reveal that Disdukcapil continues to accommodate applications for single-word names, subject to applicants signing a Statement of Absolute Responsibility (SPTJM). This practice does not give rise to any legal or administrative consequences, as no explicit sanctions are prescribed for the use of single-word names in civil registry documents. Nevertheless, Disdukcapil undertakes efforts to strengthen regulations and provide public education to enhance awareness of the importance of compliance with legal naming provisions. It is recommended that socialization activities be intensified and that public awareness be further improved. Keywords: Birth Certificate, Single-Word Name, Civil Registry Office, Responsibility "ƒ Abstrak Penelitian ini membahas praktik penerbitan akta kelahiran dengan nama satu kata di Kabupaten Sekadau, meskipun Pasal 5 Ayat (3) Permendagri No. 73 Tahun 2022 mewajibkan minimal dua kata. Fenomena ini dipengaruhi tradisi dan kepercayaan masyarakat bahwa nama panjang dapat menjadi beban atau mendatangkan penyakit, sehingga lebih sering disingkat menjadi satu kata. Metode penelitian menggunakan pendekatan empiris deskriptif dengan data dari wawancara dan angket terhadap Disdukcapil serta orang tua (periode 2022"“2025). Analisis dilakukan secara kualitatif, menghubungkan praktik di lapangan dengan aturan hukum. Hasil penelitian menunjukkan bahwa Disdukcapil tetap melayani penerbitan akta kelahiran dengan nama satu kata, dengan syarat pemohon menandatangani Surat Pernyataan Tanggung Jawab Mutlak (SPTJM). Praktik ini tidak menimbulkan akibat hukum maupun sanksi administratif karena belum ada ketentuan yang mengatur larangan secara tegas. Meski begitu, Disdukcapil berupaya melakukan edukasi dan penguatan regulasi agar masyarakat memahami pentingnya kesesuaian penamaan dengan aturan hukum. Disarankan agar sosialisasi lebih ditingkatkan dan kesadaran masyarakat semakin terbentuk. Kata Kunci: Akta Kelahiran, Nama Satu Kata, Disdukcapil, Tanggung Jawab